Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil Menengah (SAK EMKM) Dalam Penyusunan Laporan Keuangan A.D.D Tour & Travel - Alysa Valentina Sandi; Dian Imanina Burhany (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
A.D.D Tour & Travel is a service company that provides services in the form of car, bus rental and also provides various tour packages. In recording, this company has not kept records in accordance with SAK EMKM. Because the company only keeps simple records of cash receipts and disbursements. The company also has not prepared a financial report. The purpose of this study is to compile financial reports on ADD Tour & Travel based on SAK EMKM. The method used in this research is a qualitative method with a descriptive approach. And for data collection methods by means of interviews and documentation.